Project method of marketing analysis of the international market - Gliznutsa, M. Ju.; Kramskoi, D. Ju. (WSEH, 2023)
It has been proven that social networks are a proven and effective tool for collecting information about consumers and competitors, relevant for companies in many fields of activity, allowing them to see the market from the inside. SEO – search engine optimization – is a set of measures aimed at increasing the site’s position when responding to queries in search services. The main SEO activities include high-quality website content, creation of unique content, interaction with social networks, links to other resources.
Keywords: marketing analysis; international business; project method; developed competition; marketing activities; project analysis; social networks; enterprises